FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH LAHAN PASANG SURUT - Asman, Asman; Wahyuni, Eka; Asyari, Muhammad Ali Hasim (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
This research highlights the importance of rice plants for humans, especially in the context of the use of agricultural inputs in Rantau Panjang Village, such as seeds, pesticides, fertilizers, labor, as well as natural elements such as climate and geographical location, all of which influence the decline in rice production. The aim of this research is to analyze the influence and effectiveness of labor, fertilizer, seeds, pesticides and other production variables on rice growth in rainfed rice fields. This research uses a quantitative descriptive approach by utilizing production data and the number of production factors used. Data analysis was carried out using the natural logarithm function (Ln) in the Cobb-Douglas model. The analysis results show that the influence of labor on production is 0.286>0.05, the influence of pesticides is 0.201>0.05, while the influence of seeds is 0.000<0.05, and the influence of fertilizer is 0.003<0.05. The average efficiency level of production components is at 0.29 or 0<0.29<1, which indicates that farmers need to increase the utilization of production components by 71%. These findings indicate that labor and pesticides have little influence on rice production, while the use of chemical fertilizers and seeds have a significant influence. In short, rice production is highly influenced by the use of chemical fertilizers and seeds, while labor and pesticides have a lesser impact. Low technological efficiency in rice cultivation in coastal areas results in the use of less pesticides, but requires more labor, fertilizer, seeds and other production inputs. Therefore, it is important to provide training and guidance to farmers regarding better agricultural techniques and the use of relevant technology so that efficiency can be increased. Thus, it is hoped that rice production can increase without increasing production costs significantly.